2004
DOI: 10.1007/s00280-004-0819-9
|View full text |Cite
|
Sign up to set email alerts
|

cDNA microarray-based identification of genes and pathways associated with oxaliplatin resistance

Abstract: In order to identify genes whose expression is associated with resistance to the chemotherapeutic agent oxaliplatin, transcripts differentially expressed between an oxaliplatin sensitive and a stably resistant subline were compared in six independent replicates using Stanford cDNA microarrays for five cell lines. "Significance analysis of microarrays" (SAM) was used to identify genes whose expression was statistically significantly different in the sensitive versus resistant members of each cell line pair. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
33
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(36 citation statements)
references
References 16 publications
3
33
0
Order By: Relevance
“…We used four colorectal cancer cell lines and we were able to induce resistance to oxaliplatin, a drug widely used in the standard treatment of this tumor. The resulting oxaliplatin-resistant cells were not subcloned, similarly to most of the published works based on microarray analysis by using in vitro models (10,13,26). The four colorectal cancer cell lines, which showed genotypic differences such as p53 status and RER phenotype, were analyzed jointly.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…We used four colorectal cancer cell lines and we were able to induce resistance to oxaliplatin, a drug widely used in the standard treatment of this tumor. The resulting oxaliplatin-resistant cells were not subcloned, similarly to most of the published works based on microarray analysis by using in vitro models (10,13,26). The four colorectal cancer cell lines, which showed genotypic differences such as p53 status and RER phenotype, were analyzed jointly.…”
Section: Discussionmentioning
confidence: 99%
“…Thereby, our approach allows emphasizing the involvement of selected genes in general mechanisms of oxaliplatin resistance acquisition and avoids processes due to individual characteristics of a particular cell line. It is important to point out that this is one of the few studies on drug resistance that include more than one resistant cell line (26) and all of them are of the same tumor type (13).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…1,2 Clinical studies have also revealed that expression of these pumps was rarely observed and did not necessarily correlate with the outcome in colon cancer. 3 Therefore, these proteins cannot completely account for the appearance of a MDR phenotype of colon cancer and other mechanisms must be involved in this process. 5-Fluorouracil (5-FU), leucovorin and oxaliplatin (Oxa) represent a therapeutic regime (FOLFOX) commonly used in the treatment of patients with advanced colon cancer.…”
Section: Introductionmentioning
confidence: 99%